A new species of Addyme, Addyme hircicornisjuxta Yu & Cho, sp. nov. to science, from Southeast Asia - Yu, Tae-Uk; Cho, Soowon (Zootaxa, 2026)
Addyme Walker, 1863 is a genus in Phycitinae, distributed from Asia to Oceania. In this study, we present a new species belong to Addyme, Addyme hircicornisjuxta Yu & Cho, sp. nov. from Laos, and Vietnam. We provide a detailed morphological description and illustrations of the adult and male genitalia, together with comparative images of related species.